Targeting brain-eating amoebae infections - Khan, Naveed Ahmed *; Ong, Timothy Yu Yee *; Siddiqui, Ruqaiyyah Bano * (American Chemical Society, 2017)
Brain infections due to Acanthamoeba spp., Balamuthia mandrillaris, and Naegleria fowleri often lead to death. Despite diﬀerences in the preferential sites of infection in the brain, the mode of delivery of drugs is often intravenous. Here, we discuss targeted therapeutic approach to aﬀect parasite viability without aﬀecting the host cells, with an eye to improve formulation of drugs and/or administration of drugs against brain-eating amoebae.